Organic Food and Human Health: Instrumental Variables Evidence - Heinz Welsch (University of Oldenburg, Department of Economics, 2012)
Organic food markets in developed countries have been rapidly expanding in recent years. Though expected health benefits are a major motive for buying organic food (OF), the health effects of consuming OF are uncertain. This study uses survey data from Germany, 2007, to explore the causal relationship between OF consumption and self-rated health status. While it finds strong and statistically significant relationships between health and indicators of the intensity and duration of OF consumption, these relationships vanish when OF consumption is instrumented by respondents' assessment of the necessity of renewable energy. Since the instrument satisfies usual validity standards, these findings suggest that the OF-health relationship may be spurious due to common unobserved factors, in particular a health-oriented lifestyle.
Keywords: I12; D12; Q13; 330; health; food; consumption; organic agriculture; Biokost; Ernährungsverhalten; Gesundheit; Deutschland